Vývoj a proměny stranického systému na Faerských ostrovech - Brachtl, Václav (Masaryk University, 2010)
The article deals with the creation of and changes in the party system of the Faroe Islands. Sartori’s party system typology is used. Attention is also paid to the cleavages shaping the Faroese party system. The story of Faroese party politics starts at the beginning of the 20th century when the Unionist and Self-Government parties were founded. The system was influenced mainly by Faroese-Danish relations and by economic crises in the 1920s and 1990s.